The Strategies of Novice Teachers’ in the Large Class Management - Anisha Ayu Anindya; Ajeng Putri Nur Anisa; Akmal (Universitas Sulawesi Barat, 2020)
novice teachers, strategies, large class.This research reports which aimed to analyze strategies of novice teachers used in the large classroom management. This work is a comprehensive case study covering all teachers who play an important role in their classroom management. The case study on this research focused on Junior High School novice teachers in Yogyakarta. The researcher choose this school because it has large class that can support the researcher in collecting the data. The subject of this research consists of five novice teachers. The data was gathered through observation and interview. This study indicated the perspectives of the novice teachers in large classroom.The result showed that the teachers mostly divide or organize the students by grouping them, monitoring them to check students’ work and to keep the class calm, give them positive punishment to students who misbehave, and using some teaching method to make students active during the teaching and learning process.